Tracing the Deep Carbon Cycle Using Metal Stable Isotopes: Opportunities and Challenges. (June 2019) - Liu, Sheng-Ao; Li, Shu-Guang
Abstract: The subduction of marine carbonates and carbonated oceanic crust to the Earth's interior and the return of recycled carbon to the surface via volcanism may play a pivotal role in governing Earth's atmosphere, climate, and biosphere over geologic time. Identifying recycled marine carbonates and evaluating their fluxes in Earth's mantle are essential in order to obtain a complete understanding of the global deep carbon cycle (DCC). Here, we review recent advances in tracing the DCC using stable isotopes of divalent metals such as calcium (Ca), magnesium (Mg), and zinc (Zn). The three isotope systematics show great capability as tracers due to appreciable isotope differences between marine carbonate and the terrestrial mantle. Recent studies have observed anomalies of Ca, Mg, and Zn isotopes in basalts worldwide, which have been interpreted as evidence for the recycling of carbonates into the mantle, even into the mantle transition zone (410–660 km). Nevertheless, considerable challenges in determining the DCC remain because other processes can potentially fractionate isotopes in the same direction as expected for carbonate recycling; these processes include partial melting, recycling of carbonated eclogite, separation of metals and carbon, and diffusion. Discriminating between these effects has become a key issue in the study of the DCC and must be considered when interpreting any isotope anomaly of mantle-derived rocks. An ongoing evaluation on the plausibility of potential mechanisms and possible solutions for these challenges is discussed in detail in this work. Based on a comprehensive evaluation, we conclude that the large-scale Mg and Zn isotope anomalies of the Eastern China basalts were produced by recycling of Mg- and Zn-rich carbonates into their mantle source.